Pajak Penghasilan 26 - Awie Alpany BR Sitorus; Neng Risya (Kajian Ekonomi dan Akuntansi Terapan, 2025)
Income Tax Article 26 (PPh 26) is a type of tax imposed on income received by foreign taxpayers from Indonesia, including royalties, interest, dividends, prizes, as well as technical and managerial services. This study aims to analyze the implementation of Article 26 in cross-border transactions, the level of compliance by foreign taxpayers, and the effectiveness of tax withholding and payment by withholding agents. The method used is a descriptive qualitative approach through literature review and analysis of tax regulations. The results show that although the regulations concerning PPh 26 are relatively clear, there are still obstacles in its implementation, such as a lack of understanding by tax withholders, difficulties in validating foreign tax documents, and suboptimal utilization of tax treaties (Double Tax Avoidance Agreements). This research recommends enhanced education and training for withholding agents, stronger integration of digital reporting systems, and stricter supervision by tax authorities in order to maximize state revenue potential from Article 26 income tax.